Null and hypomorph Prickle1 alleles in mice phenocopy human Robinow syndrome and disrupt signaling downstream of Wnt5a - Liu, Chunqiao (The Company of Biologists, 2014)
Planar cell polarity (PCP) signaling plays a critical role in tissue morphogenesis. In mammals, disruption of three of the six “core PCP” components results in polarity-dependent defects with rotated cochlear hair cell stereocilia and open neural tube. We recently demonstrated a role of Prickle1, a core PCP molecule in Drosophila, in mammalian neuronal development. To examine Prickle1 function along a broader developmental window, we generated three mutant alleles in mice. We show that the complete loss of Prickle1 leads to systemic tissue outgrowth defects, aberrant cell organization and disruption of polarity machinery. Curiously, Prickle1 mutants recapitulate the characteristic features of human Robinow syndrome and phenocopy mouse mutants with Wnt5a or Ror2 gene defects, prompting us to explore an association of Prickle1 with the Wnt pathway. We show that Prickle1 is a proteasomal target of Wnt5a signaling and that Dvl2, a target of Wnt5a signaling, is misregulated in Prickle1 mutants. Our studies implicate Prickle1 as a key component of the Wnt-signaling pathway and suggest that Prickle1 mediates some of the WNT5A-associated genetic defects in Robinow syndrome.